2016
DOI: 10.1177/000313481608200832
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Transhiatal Esophagectomy in a Community Hospital: Evolution of Technique

Abstract: Esophageal cancer is an uncommon but highly lethal disease. Surgical resection is the gold standard of treatment for early-stage disease. Traditional surgical approach entailed significant convalescence, hospital stay, and morbidity and mortality. Transhiatal esophagectomy (THE) involves blind dissection of the esophagus with minimal mediastinal lymphadenectomy. Integration of robotic surgery is an alternate platform for minimally invasive approach while maintaining safety and following oncologic principles. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Interestingly, the authors reported using biologic mesh to reinforce the hiatus to address the issue of postoperative diaphragmatic hernias, a step rarely performed today [27,41] . Others have also reported similar outcomes [84][85][86][87] . More recently, Wecowski et al [88] prospectively reported their experience in incorporating a robotic platform for transhiatal esophagectomy.…”
Section: Outcomes Of Robotic Esophagectomymentioning
confidence: 57%
“…Interestingly, the authors reported using biologic mesh to reinforce the hiatus to address the issue of postoperative diaphragmatic hernias, a step rarely performed today [27,41] . Others have also reported similar outcomes [84][85][86][87] . More recently, Wecowski et al [88] prospectively reported their experience in incorporating a robotic platform for transhiatal esophagectomy.…”
Section: Outcomes Of Robotic Esophagectomymentioning
confidence: 57%
“…Similar issues with pulmonary complications after esophagectomy are found within both the transhiatal literature and transthoracic literature. 8,10,[13][14][15] Nearly one patient in 10 had an SSI, all of which were quite trivial and involved the incisions for the robotic trocars; some appeared after discharge and all resolved with antibiotics. This rate of SSIs seems high for our practice.…”
Section: Discussionmentioning
confidence: 99%